Factors influencing consumers’ willingness to pay under pay what you want context - Roy, R.; Rabbanee, Fazlul (2016)
Pay What You Want (PWYW) is a type of participative pricing mechanism where the buyer can offer any price including a price of zero; and the seller has to accept the price without withdrawing the product offer. Although existing research identified several variables such as altruism, price consciousness, reference price, income, and perceived fairness of the price paid to influence consumers’ willingness to pay (WTP) under PWYW context; however, many of these variables may act in complex interactive ways. To the best of our knowledge, no study tested the interaction among these variables in a PWYW context. This research examined the direct and interactive impact of product involvement, price consciousness and internal reference price on consumers’ WTP under PWYW context. It confirmed that consumers pay a significantly higher price than zero under PWYW condition. The findings of the study revealed that product involvement had a direct impact on consumers’ WTP. Further, the effect of product involvement on consumers’ WTP was found to be moderated by price consciousness. This moderation, however, took place for consumers with high internal reference price but not for consumers with low internal reference price. Managerial implications of the findings were discussed.